Modelling population responses to flow: The development of a generic fish population model. (May 2016) - Stratford, Danial S.; Pollino, Carmel A.; Brown, Alice E.
Abstract: Many fish species are dependent upon flows to trigger breeding, facilitate high recruitment of offspring, and to maintain adult survival rates. Understanding how fish populations respond to different flow regimes is important in regulated waterways as subtle changes in regimes have the potential to influence both fish breeding and survival. In this paper, we describe an age-structured population response model that explores how quantitative changes in the flow regime can lead to changes in fish population size and structure through time. We use three large bodied fish species (golden perch, Murray cod and the invasive common carp) from the mid Murray River near Barmah-Millewa Forest to explore the possible responses to the observed flow regime over a 30-year period. The model links flow volumes, seasonality, temperature and rates of fall to the fecundity and survival rates for the different fish species to project population change through time. Highlights: We have developed a fish population response model to evaluate flow regimes. The model uses daily flow and water temperature to determine population response. Population response is modelled using an age-structured matrix model. Model outputs are explored with sensitivity analysis and provisional confirmation.